An empirical assessment of how the government policies influenced the performance of the SMEs in Zimbabwe - Godfrey Tambudzayi Musabayana; Emmanuel Mutambara; Tony Ngwenya (Journal of Innovation and Entrepreneurship, 2022)
The government policy framework provides the roadmap that can be used to implement the enacted policies to support the performance of SMEs. The Zimbabwean government came up with sound policies that were deliberately crafted to improve the performance of SMEs, but the main challenge was on the communication, implementation and support of the policies hence their impact was highly insignificant. This study established the extent to which how the government policies were effective in influencing the performance of SMEs in Zimbabwe. The study used mixed research method following the sequential exploratory strategy. The findings of this study indicate that the government managed to inform the elite group, its officers who are well versed with SME policies and government intentions were clearly communicated to all the experts in the SME sector, but this information did not cascade down to the SME implementers. The findings will assist the government to re-focus and develop a new strategic framework that will bring on board all the stakeholders in the SME sector. From the findings of the study, the researcher deduces that the poor performance of Zimbabwean SMEs is basically an issue of the government which failed to communicate its intentions to the implementers and this had a ripple negative effect across the whole economy of the country.
Keywords: 650; Government policy; SME implementers; SME performance